Model Pembelajaran Rollenspiel untuk Meningkatkan Keterampilan Berbicara Bahasa Jerman Siswa - Irmawati Irmawati; Misnah Mannahali (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2019)
The purpose of this study was to know the effectiveness of  the Rollenspiel model in increasing student’s speaking German skill. This study used quasy-experiment approach. Data was collected using speaking skill test. The sample in this study was random sampling, namely students of class XI IPA 1 which amounted to 20 students as an experimental class and students of class XI IPA 2 totaling 21 students as a control class. Data were analyzed by using t-Test analysis. The result of data analysis shows that th 4,28> tt 2,023 at significant level of 0.05. The results showed that Rollenspiel learning model is effectively used in the skill of speaking of German.